Determinants of bank profitability in the European Union - Strantzis, Dimitrios (2020)
By using an unbalanced panel data set, the aim of this paper is to analyze the impact of bank-specific, industry-level and macroeconomic factors upon the profitability of 90 commercial banks operating in the European Union, over the period 2009-2019. This study also attempts to examine separately the profitability of domestic and foreign banks. Fixed effects models are created and Return on Average Assets (ROAA) is used as a proxy for bank profitability. The results indicate that, regardless of ownership, profitability of banks is significantly affected by capital adequacy, management efficiency and GDP growth. In all cases, the only variable, which is not significantly associated with bank profitability, is the inflation rate. It is also interesting that although all the variables have the same relationship with banks’ performance in all cases, there is an exception with bank size. Bank size has a positive relationship with profitability of domestic banks whereas a negative relationship is observed when foreign banks are considered.